Convergence without Equity : A Closer Look at Spatial Disparities in Russia - World Bank Group (World Bank, Washington, DC, 2018)
Addressing regional disparities is key to unlocking Russia’s potential to achieve stronger gains in growth and equity outcomes as well as to improve its institutional environment. While spatial disparities have been an important policy concern in Russia for a long time, inequalities across its vast territory remain stark. This report explores the current state of regional disparities at the macro and micro-level, updating existing literature to reflect recent trends and providing new insights into household-level drivers of welfare. The report stresses that addressing spatial disparities does not necessary imply “balancing” growth across a geographic territory – but rather focusing on creating opportunities for all people, regardless of where they live.